Pembuatan LKPD berbasis model discovery learning bermuatan nilai-nilai karakter untuk meningkatkan kompetensi fisika peserta didik pada materi usaha dan energi, momentum dan impuls - Afriza Rusni; Prof.Dr.Festiyed,M.S Festiyed; Dr.Masril,M.Si Masril (Universitas Negeri Padang, 2019)
LKPD is one type of teaching material that is used as a learning resource in the implementation of education in schools, including in learning Physics. The reality in school, in the learning process that occurs specifically in Physics subjects, is that learning outcomes are still low. One of the reasons for using the LKPD used is not optimal. The noble character demanded by the curriculum has also not been seen in the LKPD. Besides that the LKPD used is not based on the Discovery Learning model optimally. One teaching material that can overcome this problem is LKPD based on the Discovery Learning model with character values. The purpose of this study was to produce LKPD based on the Discovery Learning model with character values to improve students' physical competencies in business material and energy, momentum and impulses. This type of research is research and development (Research and Development) with the object of research is LKPD based on the Discovery Learning model containing character values. The instrument of data collection in this study is a validity sheet for experts to determine product validity. Practical sheets for students in the form of questionnaires to determine the practicality of LKPD based on Discovery Learning models with character values in learning. Based on data analysis, two results of this study can be stated. First, LKPD based on Discovery Learning models containing character values in business and energy and momentum and impulse material are valid and appropriate to use in the learning process of Physics. This is indicated by the average validity of experts and practitioners respectively 86.76 and 96.19. Teaching materials also have good descriptions. Second, the use of these Physics teaching materials in the learning of class X high school students is practical with an average practicality value of 81.02.